Analisis Kinerja Electrostatic Precipitator (ESP) Berdasarkan Pembagian Besarnya Arus Transformator Di PT PJB UBJOM PLTU Paiton - jon, winarno (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2020)
Electrostatic Precipitator (ESP) is a device that has the function of capturing the ashes of combustion contained in the exhaust gases before being discharged into the atmosphere through a stack / chimney, so that the discharged gases to be discharged do not contain ash particles that can pollute the environment. PT PJB UBJOM PLTU Paiton has 16 ESP transformers operating 24 hours. During the operating period there are disturbances and damage that causes ESP efficiency is reduced so there is a need to reset the transformer secondary current. It is intended that the efficiency of ESP is maintained and the exhaust gas does not pollute the environment. By using the "5 Whys or RCPS (Root Cause problem solving)" method, the researcher knows the causes of disturbances and damage to the ESP transformer and provides recommendations for the configuration of the current used by the ESP transformer to improve its efficiency when disturbances or damage occurs. The cause of disruption and damage to the ESP transformer consists of 3 factors: the method / method used, human and machine / equipment. The magnitude of the Electrostatic Precipitator (ESP) efficiency during faults and damage varies depending on the amount of current in the ESP transformer. The greater the current, the greater the magnetic field strength so that the greater the ESP efficiency value. Although there is less efficiency (below 90%), with the right transformer secondary current configuration, efficiency can be maintained close to the design. The efficiency of ESP on March 18, 2019 increased from 88.23% to 90.58%. The efficiency of ESP on March 30, 2019 increased from 89.71% to 90.55%. The efficiency of ESP on June 10, 2019 increased from 84.38% to 93.63%. The efficiency of ESP on June 13, 2019 increased from 87.38% to 91.92%. ESP efficiency on June 24, 2019 increased from 85.83% to 90.03%